EXTERNAL RADIOTHERAPY PROCEDURE OF THYROID CANCER WITH MASS MALIGNANT THYROID IN RADIOTHERAPY INSTALATION FACILITY OF RSUD DR. MOEWARDI SURAKARTA - Himawan Setyono; Darmini Darmini; Khumaidi Khumaidi; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2018)
Background: External radiotherapy for thyroid cancer, generally was conducted with 3 exposure area technique, where as in thyroid cancer case with mass malignant thyroid, treatment in Radiotherapy installation facility of RSUD Dr. Moewardi Surakarta used different technique that was by five exposure area in two step. The purposes of this researchwerte to know radiotherapy treatment of thyroid cancer with mass malignant thyroid, the reason of two step exposure and the reason of using direct AP-PA exposure area.Methods: The method of this research was qualitative researchwith case study approachment by observing, interviewing with radiation oncologist doctor, radiotherapy radiographer and medical physicist, and reviewing patient medical record document, simulator image data, treatment planing system resultand patient exposure data. For data analyzing, researcher used interactive model.Results: The result of this research showed that external radiotherapy for thyroid cancer with mass malignant thyroid in radiotherapy installation facility of RSUD Dr. Moewardi Surakarta is using convensional simulator, teleterapy Cobalt-60 machine, and five exposure area technique in twop step exposure. The first step was AP-PA direct exposure and second step were AP supraclavicula and left-right lateral.Conclusion: The reason of two step exposure technique use is for optimalization of therapeutic ratio, whereas the purpose of AP-PA exposure area in this technique is to maximizing dose on mass.